二十世纪七八十年代新华女性小说作者的世界 = The worlds of Singapore Chinese female writers of fiction : a study of short stories and novellas during the seventies and eighties from a feminist perspective - 胡月宝 Aw, Guat Poh (2015)
This dissertation is a comprehensive study of Singapore Chinese female writers' short stories and novellas from 1970 to 1989. The idea of the four coordinates of artist/writer, text, universe/world, and audience/reader in Literary creation/criticism as proposed by M.H. Abrams and modified by James J.Y. Liu is adopted as an organizing framework. The concepts of diachronic and synchronic used in linguistics are also incorporated. The dissertation includes 283 short stories and novellas. From a feminist perspective, the study focuses on the three “worlds" of Singapore Chinese female writers: namely, the diachronic, the synchronic and the textual worlds. It comprises seven chapters. The first chapter begins with a definition or key terms and concepts in the dissertation. A brief introduction to Singapore Chinese literature in general and Singapore Chinese female literature in particular is provided in the course. This is followed by an explanation of the theoretical framework of the dissertation and its structure. The second and third chapters focus on the diachronic and synchronic worlds of Singapore Chinese female writers. The second chapter examines the status of Singapore women from 1819 to 1969. Special attention is paid to the status of Singapore Chinese women. The aim is to explore into their diachronic world. The third chapter looks into their synchronic world. The changes in women' s status from 1970 to 1989 are-outlined and analyzed. The cultural, economical, educational as when legal statuses of women are reviewed. These chapters serve to lay a foundation for us to examine how the realistic diachronic and synchronic worlds will influence the textual world of Singapore Chinese female writers. Chapters four to six form the main theme of the dissertation. Chapter four discusses the influences of both the diachronic and synchronic worlds on the textual world of Singapore Chinese female writers in general while chapters five and six explores into the private and public spheres of Singapore Chinese women as reflected the textual world in particular. The subject matters, themes and the literary techniques and language use are dealt with in chapter four. Chapter five highlights the private sphere where the themes of love and marriage are dominant. Chapter six probes into the public sphere, where the social domain is the focus. The last chapter, the Conclusion, re-examines the textual world of Singapore Chinese female writers from a feminist perspective.